Healthcare Analytics Using Big Data for Evaluation and Extreme Machine Learning Based on MapReduce - Ramesh, R.; Selvam, V. (Indian Journal of Computer Science, 2023)
The present study focuses on Extreme Machine Learning Method (ELM), which may be used with Support Vector Machines that are optimised by Cuckoo Search to produce a method for identifying disease risk (CS-SVM). It also considers the accuracy and scalability of big data models, which considerably increase the processing power of the proposed method and produce better outcomes in terms of performance metrics like veracity and efficiency. In terms of additional performance metrics like Precision, Recall, and Average Area Under Curve, the suggested method is also compared to comparable cutting-edge methods.